2004
DOI: 10.1051/0004-6361:20034252
|View full text |Cite
|
Sign up to set email alerts
|

Intensity variations in EIT shutterless mode: Waves or flows?

Abstract: Abstract. On 11 July 2001 an EIT shutterless campaign was conducted which provided 120 high-cadence (68 s) 304 Å images of the north eastern quarter of the Sun. The most interesting feature seen in the data is an off-limb half loop structure along which systematic intensity variations are seen which appear to propagate from the top of the loop towards its footpoint. We investigate the underlying cause of these propagating disturbances, i.e. whether they are caused by waves or by plasma flows. First we identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
85
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(97 citation statements)
references
References 19 publications
12
85
0
Order By: Relevance
“…It is almost certainly responsible for prominences (Antiochos & Klimchuk 1991;Karpen et al 2006), and it may also explain "catastrophic cooling events," including coronal rain (Schrijver 2001;De Groof et al 2004;O'Shea et al 2007). During these events, a cold "blob" condenses out of the hot corona at the top of a loop.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is almost certainly responsible for prominences (Antiochos & Klimchuk 1991;Karpen et al 2006), and it may also explain "catastrophic cooling events," including coronal rain (Schrijver 2001;De Groof et al 2004;O'Shea et al 2007). During these events, a cold "blob" condenses out of the hot corona at the top of a loop.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts sharply with observed loops, which tend to have a far more uniform appearance. Falling bright knots are sometimes observed, but these are only detected at much cooler temperatures ( 0.1 MK) (Schrijver 2001;De Groof et al 2004;O'Shea et al 2007). We return to the subject of these knots later in Section 4.…”
Section: Intensitymentioning
confidence: 98%
“…There is some observational evidence of nanoflares in the coronal X-ray emission (Katsukawa & Tsuneta 2001;Schmelz et al 2009). The bright points in coronal EUV lines (Madjarska et al 2003;Tian et al 2008) and the phenomenon of coronal rain (De Groof et al 2004;Antolin et al 2010) may also be associated with nanoflares. But the firm observational evidence of nanoflare heating of the solar corona is still absent.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the hot plasma then can be quickly cooled down to the transition region or chromospheric temperatures owing to "catastrophic cooling" (Antiochos & Klimchuk 1991;Schrijver 2001;Müller et al 2003Müller et al , 2004Karpen et al 2006;Klimchuk et al 2010). The resulting dense and cool plasma blobs may then be attracted by gravity, slide down along the magnetic field lines, and result in "coronal rain" (De Groof et al 2004;Antolin et al 2010). In addition, such a compressible perturbation would generate an outgoing magnetoacoustic wave (Longcope & Priest 2007), which can be subject to steepening.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, thermal non-equilibrium may produce plasma flows, the formation of condensations, and the loss of connection between electron temperature and the ionization status of a plasma. Thermal non-equilibrium has been suggested to be responsible for the formation of prominences from coronal loops (e.g., Antiochos 1980; Karpen et al 2006, and references therein) and intensity variations traveling along the loop structure (Müller et al 2005) observed with the He ii SOHO/EIT band (De Groof et al 2004). Also, it has been recently suggested as a possible explanation of the main observational properties of coronal loops, including lifetime, temperature and density profiles, and filamentary structure (Klimchuk et al 2010).…”
Section: Introductionmentioning
confidence: 99%